Att göra folkmusik: Lärares praxis på låtkurser i svensk traditionell musik - Eriksson, Karin L. (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2021)
Workshops in Swedish folk music are occasions where what is perceived as folk music is concretized through the participants’ practice. This is especially clear when the teachers’ practice is studied based on questions about what is taught, how the teaching is carried out and how the repertoire is presented. Based on field studies conducted 2013–2015 through film documentation with follow-up interviews, the article discusses teachers’ practice in the workshops. The results show that the teachers’ practice reinforces already established norms, ideals and notions of what characterizes Swedish folk music as a genre, such as rootedness in history, mainly oral transmission and a focus on polska (a type of dance tune in triple time) that should be performed in a variable manner. The results also show that there is a potential for altering these norms; this is not, however, done to any greater degree. The teachers’ didactic choices in the workshops thus interact and fill the concept of “folk music” with a content as well as give guidelines for how to behave as a member of the Swedish folk music community of practice.